Tattoos, blood‐borne viruses and blood donors: a blood donor cohort and risk assessment. Issue 7 (8th August 2019) - Hoad, Veronica C.; Guy, Rebecca J.; Seed, Clive R.; Harley, Robert
Abstract : Background and objectives: There is conflicting evidence in the literature as to whether there is a blood‐borne virus (BBV) risk associated with tattoos in licensed premises. However, blood donors are currently deferred from blood donation in Australia for 4 months after any tattoo. We aimed to assess the incidence of BBVs in blood donors who declared tattoos and evaluate the risk to blood safety through risk modelling. Materials and methods: Donors from 2013 to 2016 with a tattoo deferral on their blood donor file with pre‐ and post‐BBV testing were analysed to determine an incidence of BBVs using standard methods. This was compared to a 2014 cohort of whole blood donors with a deferral of 4 months due to travel to a malaria‐endemic area. Using the incidence of tattoos and BBV risk, the total residual risk estimate of allowing tattooed donors to return without restriction was calculated. Results: The incidence rate of BBVs in blood donors following tattoo deferral was 13·26 (95% CI 2·67–38·75) per 100 000 person‐years (all were hepatitis C infections in males compared to 9·26 (95% CI 2·49–23·71) per 100 000 in blood donors following malaria deferral. If other risk factors were accounted for the risk in tattoo donors decreased to 4·4 per 100 000 person‐years. The total residual risk calculation if donors with a tattoo were allowed to donate without restriction was estimated at 1 in 34 million. Conclusions: This residual risk indicates BBV deferral for donors post‐tattoo in Australia is not required for blood safety.